The Lived Experience of Working Mothers Who Intended to Continue Exclusive Breastfeeding Upon the Return to Work in Saudi Arabia: An Interpretative Phenomenology Analysis Study - Alsulimani, Manar Mohammad (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2025)
Background: The World Health Organisation (WHO) recommends exclusive breastfeeding (EBF) for infants during their first six months of life. A mother's ability to maintain the EBF for the recommended duration is often impacted by obstacles such as returning early to employment. Previous research has identified a lack of lactation facilities and short maternity leave as factors that contribute to the early cessation of EBF. A review of the literature underscored the need for additional research to examine the EBF experiences of working mothers following their return to work. Additionally, there is a lack of studies investigating factors influencing the EBF practices of working mothers in Saudi Arabia who returned to work before six months post-partum. Aim: The study aimed to explore the lived experiences of Saudi working mothers who intended to continue EBF upon their return to work after paid maternity leave. Methods: Interpretative phenomenological analysis (IPA) framework was used, to explore the experiences of 14 Saudi working mothers in the health and education sectors. Participants, who had between ten to twelve weeks of maternity leave, were interviewed between March and May 2022 using purposive and snowball sampling. All participants had intended to continue EBF for up to six months after returning to work. Semi structured interviews were conducted, and IPA was utilised for data analysis. The study received ethical approval from TCD, UQU, MCH, and the General Administration of Education in Saudi Arabia. Findings: Three key themes emerged: i) Navigating EBF; ii) The Realities of EBF After Returning to Work; and iii) Resilience in Longer EBF Journeys. The study identified policy gaps, inadequate breastfeeding facilities, and inflexible breastfeeding breaks as significant barriers to continuing EBF. However, most participants who prolonged their v EBF journey despite workplace barriers demonstrated strong commitment and resilience, significantly driven by their faith in Allah, the support of their social networks, and proactive strategic planning. Conclusion: This study makes a several unique contributions to Saudi literature and adds to the existing body of international research. It enhances understanding of the EBF experiences of working mothers in the distinct context of Saudi Arabia, highlighting the need for a comprehensive strategy to support EBF working mothers in the country. This includes addressing workplace challenges, implementing supportive workplace policies, strengthening healthcare support, normalising EBF within families and society through raising awareness to facilitate a smoother transition for EBF working mothers returning to work after maternity leave.
APPROVED
Keywords: Lived experience; Exclusive breastfeeding; Working mothers; Maternity leave; EBF barriers; Saudi Arabia; IPA